Emergence of Clinical Clostridioides difficile Isolates With Decreased Susceptibility to Vancomycin. (11th December 2021) - Darkoh, Charles; Keita, Kadiatou; Odo, Chioma; Oyaro, Micah; Brown, Eric L; Arias, Cesar A; Hanson, Blake M; DuPont, Herbert L
Abstract: Background: Clostridioides difficile infection (CDI) is a leading cause of hospital-associated antibiotic-related diarrhea and deaths worldwide. Vancomycin is one of the few antibiotics recommended for both nonsevere and severe CDI cases. We sought to determine whether vancomycin nonsusceptible C. difficile strains are circulating in the patient population. Methods: Stool samples from patients with CDI were collected from 438 and 98 patients at a large university hospital in Houston, Texas, and Nairobi, Kenya, respectively. The stools were examined for the presence of vancomycin and metronidazole nonsusceptible C. difficile using broth dilution culture, Etest (BioMérieux, France), polymerase chain reaction (PCR), whole-genome sequencing, and in vivo testing in a CDI mouse model. Results: Of the Houston stool samples, 114/438 (26%) had vancomycin nonsusceptible C. difficile isolates and 128/438 (29%) were metronidazole nonsusceptible. Similarly, 66 out of 98 (67%) and 83/98 (85%) of the Nairobi patients harbored vancomycin and metronidazole nonsusceptible isolates, respectively. Vancomycin treatment of a CDI mouse model infected with a vancomycin nonsusceptible isolate failed to eradicate the infection. Whole-genome sequencing analyses did not identify vanA genes, suggesting a different mechanism of resistance. Conclusions: C. difficile strains exhibiting reduced susceptibility to vancomycin are currently circulating in patient populations. The spread of strains resistance to vancomycin, a first-line antibiotic for CDI, poses a serious therapeutic challenge. Routine susceptibility testing may be necessary. Abstract : Vancomycin is a front-line antibiotic for the treatment of Clostridioides difficile infections. However, C. difficile isolates exhibiting reduced susceptibility to vancomycin are emerging in clinical settings, posing serious clinical and public health threats.